Advanced control strategies for level system: the application of simulink for PID system: article - Yusop, Yusliana; Aziz, Noorhaliza (2017)
Any processes that have dynamics behavior and time delay makes the process difficult to be controlled. However, this type of processes are widely exist in our industries thus makes it important for us to control it regardless of the difficulties faces. The important of control system in today industries have a great impact on the emerging of new tuning method. Despite that, proportional, integral and derivative (PID) controllers still have been used in vast chemical process industries due to their robustness, simplicity and successful practical application. There are many proposed tuning methods for PID controllers to replace the conventional PID controllers. Thus, this paper presents the study of two advanced tuning methods, internal model control (IMC) and direct synthesis (DS) based on PID for controlling level system. The performances for both tuning methods are being compared justify the effectiveness of both tuning method. The selection of the most suitable value of closed-loop time constant is the main concern since it is the essential tuning parameter for enhancing the transient and steady state behavior for the process output. The higher value of time constant results in a better performance. The study shows that DS and IMC produces an identical results. In helping to decide the best tuning method of identical DS and IMC, integral of the absolute value of the error (IAE) has been used. The results showed DS tuning method provide better performance compared to IMC tuning method.